Because digital writing matters : improving student writing in online and multimedia environments - DeVoss, Danielle Nicole; Eidman-Aadahl, Elyse; Hicks, Troy; National Writing Project (U.S.) (San Francisco : Jossey-Bass, 2010)
'How to apply digital writing skills effectively in the classroom, from the prestigious National Writing Project As many teachers know, students may be adept at text messaging and communicating online but do not know how to craft a basic essay. In the classroom, students are increasingly required to create web-based or multi-media productions that also include writing. Since writing in and for the online realm often defies standard writing conventions, this book defines digital writing and examines how best to integrate new technologies into writing instruction. Shows how to integrate new technologies into classroom lessons. Addresses the proliferation of writing in the digital age. Offers a guide for improving students' online writing skills. The book is an important manual for understanding this new frontier of writing for teachers, school leaders, university faculty, and teacher educators.'--Provided by publisher
Includes bibliographical references (p. 160-166) and index
Keywords: English language -- Rhetoric -- Computer-assisted instruction; English language -- Rhetoric -- Study and teaching; English language -- Composition and exercises -- Computer-assisted instruction; English language -- Composition and exercises -- Study and teaching; Report writing -- Computer-assisted instruction; Report writing -- Study and teaching; Electronic portfolios in education; Multimedia systems